Sikap dan keperluan latihan bagi pengawal keselamatan UNIMAS - Thian, Vui Shau (2003)
The study was carried out in Universiti Malaysia Sarawak (UNIMAS) which emphasizes on quality of service. This research studies the present job performance of security guards in Unimas and their attitudes. Security guards in Unimas play an important role to make sure that people and properties in the university are in safety condition.